THE RELATIONSHIP BETWEEN BASIC SANITATION AND FLY DENSITY LEVELS AT RESTAURANTS IN THE WORKING AREA OF THE LAMPULO HEALTH CENTER, KOTA BANDA ACEH IN 2021 - Andriani, Novi; Ariscasari, Putri; Mawardi, Mawardi; Mairani, Tiara (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: The main factor in a restaurant that must always be maintained is the hygiene and sanitation of the restaurant. Based on the results of observations in several restaurants in the working area of the Lampulo Community Health Center,it can be seen that the sanitation of restaurants does not meet standards, such as the condition of the equipment washing facilities that are not suitable for use, the absence of special trash cans, the absence of covers for prepared food and the absence of facilities for prevention fly. This research aims to determine the relationship between basic sanitation and the level of fly density at restaurants in the Lampulo Community Health Center Working Area, Kota Banda Aceh in 2021. Method: The research is descriptive analytical with a cross- sectional design. Sampling was taken using a total sampling method of of 50 restaurants. Data analysis used the Chi Square test with the STATA 13 computer program. Results: The results showed that 55.8% of restaurants had a high fly density level. The results of the bivariate analysis show that there is a relationship between ready-made food storage places (p value = 0.019), equipment washing places (p value= 0.013), rubbish disposal places (p value= 0.003), and fly prevention facilities (p value= 0.001). Recommendation: Restaurant owners to improve sanitation facilities in restaurants, maintain environmental cleanliness, and implement health requirements in restaurants.